The complexity of porphyrin-like pigments in a marine annelid sheds new light on haem metabolism in aquatic invertebrates - Martins, C. (2019)
PTDC/MAR-BIO/0113/2014. UID/Multi/04378/2019. UID/QUI/50006/2019. SFRH/BD/120030/2016. SFRH/BD/109462/2015. IF/00265/2015.